An investigation into the effect of play-based instruction on the development of play skills and oral language. (December 2016) - Stagnitti, Karen; Bailey, Alison; Hudspeth Stevenson, Edwina; Reynolds, Emily; Kidd, Evan
The current study investigated the influence of a play-based curriculum on the development of pretend play skills and oral language in children attending their first year of formal schooling. In this quasi-experimental design, two groups of children were followed longitudinally across the first 6 months of their first year at school. The children in the experimental group were attending a school with a play-based curriculum; the children in the control group were attending schools following a traditional curriculum. A total of 54 children (Time 1 M age  = 5;6, range: 4;10–6;2 years) completed standardised measures of pretend play and narrative language skills upon school entry and again 6 months later. The results showed that the children in the play-based group significantly improved on all measures, whereas the children in the traditional group did not. A subset of the sample of children ( N  = 28, Time 1 M age  = 5;7, range: 5;2 – 6;1) also completed additional measures of vocabulary and grammar knowledge, and a test of non-verbal IQ. The results suggested that, in addition to improving play skills and narrative language ability, the play-based curriculum also had a positive influence on the acquisition of grammar.